Functional Foods, Nutraceuticals and Probiotics: A Focus on Human Health - Morayma Ramírez Damián; Naima G. Cortes-Perez; Erika T. Quintana; Alicia Ortiz-Moreno; Cynthia Garfias Noguez; Carlos Eugenio Cruceño-Casarrubias; María Elena Sánchez Pardo; Luis G. Bermúdez-Humarán (Microorganisms, 2022)
Functional foods are classified as traditional or staple foods that provide an essential nutritional level and share potentially positive effects on host health, including the reduction of disease by optimizing the immune system’s ability to prevent and control infections by pathogens, as well as pathologies that cause functional alterations in the host. This chapter reviews the most recent research and advances in this area and discusses some perspectives on what the future holds in this area.